PENJADWALAN PERAWAT BERDASARKAN MINIMASI PELANGGARAN PERATURAN DAN MINIMASI BIAYA LEMBUR - Silalahi, Agustinus; Lydia, Antonia; Natalia, Christine; Prasetya, Wibawa (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2022)
The high overtime cost for nurses from Manual Scheduling, in the inpatient unit at ABC Hospital, where the overtime cost was Rp.10,409,910,-, much the difference number working hours between each nurses and many violations of hard constraint. So, it is necessary to make improvements to the scheduling. This study developed the scheduling whose goal is to minimize violations of regulations and minimize overtime costs by Goal Programming (GP). Mathematical formulation for both objectives were solved by LINGO 18.0. The difference in the number of working hours between the highest working hours and the least working hours for nurses who are not on leave, on Manual Scheduling, The Minimizing Regulatory Violations Scheduling and The Minimizing Overtime Costs Scheduling were 53, 0 and 1 hour(s) respectively. The highest number of working hours was 221 hours in Manual Scheduling, while the least number working hours was 175 hours in Minimizing Overtime Scheduling. If the policy in scheduling wanted to minimize violations, using the result of Scheduling for Minimizing Violation of the regulations there were 177 violations and overtime costs was Rp. 3.652.600,- reduced by 64.91%. Meanwhile, if the Hospital wanted to minimize overtime costs, using the result of Scheduling Minimizing Overtime Costs, there were 246 violations and overtime costs was Rp.104,360,- reduced by 99.0%.In the future, the hospital must establish a policy in terms of scheduling, whether the aim is to minimize violations of regulations or minimize overtime costs, so that based on this policy, the mathematical formulation can be determined.